P020: Impact of dexamethasone dose on return visits at a tertiary pediatric emergency department. (May 2019) - Cherry, J.; Fitzpatrick, E.; Slaunwhite, E.; Hurley, K.
Abstract : Introduction : Croup is a common viral upper airway infection in children aged 6 months to 6 years. Although a single dose of dexamethasone decreases return visits, the prescribed dose varies from 0.15mg/kg to 0.6mg/kg. Our objective was to examine the effect of varied dexamethasone dosing on unplanned return ED visits for croup.Methods : This was a retrospective chart review of IWK ED patient treatment records from September 1, 2014 – August 31, 2016 of children aged 6 months to 6 years with an ICD-10 discharge diagnosis code of croup. Data were abstracted by trained research assistants using a structured data collection form in REDCap. A sample of 5% of charts had double data abstraction to test for agreement. Our primary outcome was return visits to the ED within 7 days. Secondary outcomes were ED length of stay (LOS), admission to hospital and admission to the pediatric intensive care unit (PICU). Data were analyzed using descriptive statistics and chi-square for between group comparisons.Results : The dataset included 1595 patient visits for croup. Data analysis is in progress. Triage acuity as per CTAS included: resuscitation n = 5; emergent n = 351; urgent n = 558; less urgent n = 605; and, non-urgent n = 2. Most patients had no co-morbid conditions (n = 1548). Dexamethasone dosing varied: 0.15 mg/kg n = 64; 0.3 mg/kg n = 838; and, 0.6 mg/kg n = 493. ED LOS was under 1 hour in 483 patients, 1-3 hours in 805, 3-6 hours in 225 and 6-12 hours in 9 patients. Few patients were admitted to hospital (n = 22) and no patients were admitted to PICU. Within 7 days of the index visit, 78 patients had an unplanned return visit to the ED for croup.Conclusion : The data analysis is in progress. This study will inform our future research on a practice change in our ED to comply with the dose of dexamethasone recommended by the Canadian Pediatric Society for the treatment of croup in 2017.